PERIKATAN YANG DILAHIRKAN DARI SEBUAH PERJANJIAN BERDASARKAN PASAL 1332 KUHPERDATA TENTANG BARANG DAPAT MENJADI OBJEK PERJANJIAN - Deny Fernatha (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
ABSTRACT Engagement is a legal relationship between two parties in the field of assets, where one party (creditor) has the right to achievement, and the other party (debtor) is obliged to fulfill the pertasi. According to article 1338 of the Civil Code that an agreement made legally, ie fulfilling the requirements of article 1320 of the Civil Code, applies as a law to those who make it, irrevocable without the agreement of both parties or due to sufficient reasons according to the law and must be carried out in good faith. the author is interested in raising this issue in a paper entitled. The Orientation About Commitments That Are Born From An Agreement Referring to Article 1332 of the Civil Code Regarding Goods may be the object of the Agreement. In this study, the type of research used is normative legal research or library research. An engagement can be born from an agreement and law. In other words, an agreement made can lead to an engagement for the parties that made the agreement. That objects traded in the public interest cannot be used as objects of the agreement. Authors' advice In any case, we are allowed to enter into agreements, but clearly, we must not contradict what has been contained in Article 1337 of the Civil Code that every object we promise is not may conflict with law, decency and public order. Keywords: Engagement, Material, and Agreement